2012
DOI: 10.1017/s1368980012004983
|View full text |Cite
|
Sign up to set email alerts
|

Dietary risk factors for the development of insulin resistance in adolescent girls: a 3-year prospective study

Abstract: Objective: Identifying risk factors for insulin resistance in adolescence could provide valuable information for early prevention. The study sought to identify risk factors for changes in insulin resistance and fasting blood glucose levels. Design: Prospective cohort of girls participating in the National Heart, Lung, and Blood Institute Growth and Health Study. Setting: USA. Subjects: Adolescent girls (n 774) assessed at the ages of 16-17 and 18-19 years. Over a 3-year period, measurements of fasting blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
0
21
0
2
Order By: Relevance
“…Nutritional factors have been associated with IR and related inflammatory states in different populations [27,28]. In the studied population, participants with IR showed significantly higher consumptions of simple carbohydrates and dietary cholesterol and low intakes of dietary fiber than their NIR counterparts.…”
Section: Discussionmentioning
confidence: 93%
“…Nutritional factors have been associated with IR and related inflammatory states in different populations [27,28]. In the studied population, participants with IR showed significantly higher consumptions of simple carbohydrates and dietary cholesterol and low intakes of dietary fiber than their NIR counterparts.…”
Section: Discussionmentioning
confidence: 93%
“…After grouping studies in accordance with outcomes of interest, one cross-sectional study (56) Fibre in childhoodinvestigating dietary fibre intake and folate status and one repeated publication (57) were excluded. Additionally, after performing adapted search commands on other databases and scanning the reference lists from included studies, two further cross-sectional studies (70,71) and five prospective cohort (64,(72)(73)(74)(75) studies were identified and included. In total, fifteen cross-sectional studies and eleven cohort studies were included in the present review.…”
Section: Search Strategymentioning
confidence: 99%
“…This situation constitutes a primary risk factor for the development of insulin resistance (IR), which is a phenomenon that plays a major role in the emergence of cardiometabolic disorders. 3 Dietary components can also influence insulin sensitivity. Evidence indicates a positive association between IR and the excessive intake of energy-dense foods rich in simple carbohydrates and fats, especially saturated and trans fats.…”
Section: Introductionmentioning
confidence: 99%